Photochemical generation of bis-hexahapto chromium interconnects between the graphene surfaces of single-walled carbon nanotubes. Issue 1 (17th November 2014) - Pekker, Aron; Chen, Mingguang; Bekyarova, Elena; Haddon, Robert C.
Abstract : The linkage of single-walled carbon nanotube junctions by the photochemistry of organometallic chromium reagents produces dramatic increases in network conductivity. Abstract : The electrical conductivity of single-walled carbon nanotube (SWNT) networks is strongly enhanced by the high vacuum e-beam deposition of transition metals. In the present communication we demonstrate that it is possible to accomplish the same chemical functionalization reactions at room temperature beginning with simple organometallic precursors. We show that the photochemically induced reactions of solutions of Cr(CO)6, Cr(η 6 -benzene)(CO)3, and Cr(η 6 -benzene)2 with thin films of semiconducting, metallic and non-separated SWNT films all lead to strongly enhanced conductivities which produce consistent results for each SWNT type among the three organometallic reagents. We conclude that all three of these reactions lead to the generation of covalent (η 6 -SWNT)Cr(η 6 -SWNT) interconnects which provide conducting pathways in the SWNT films and our results broaden the applicability of the transition metal bis-hexahapto-bond as an electronically conjugating linkage between graphene surfaces.